Predicting animal abuse behaviors with externalizing and psychopathic personality traits. (March 2021) - Rock, Rachel C.; Haugh, Stephanie; Davis, Kelci C.; Anderson, Jaime L.; Johnson, Alexandria K.; Jones, Michelle A.; Salekin, Randall T.
Abstract: For years, researchers have tried to explain predictive features of psychopathic behavior and externalizing personality traits (Stupperich & Strack, 2016). Among this list is animal abuse. Although animal abuse is commonly linked with psychopathy, previous studies have provided mixed results regarding this relationship and its predictive features (Arluke & Madfis, 2014; Ascione & Shapiro, 2009). The debate on this relationship has led to questions about whether animal abuse could have a stronger connection to a particular facet of psychopathy, rather than the broader construct (Dadds, Whiting, & Hawes, 2006). Therefore, literature calls for examination of the possible link between animal abuse and psychopathy, as well as other externalizing personality traits, which the current study aims to assess. We examined the relationship between psychopathy, as measured by the Psychopathy Checklist- Short Version (PCL:SV; Hart, Cox, & Hare, 1995), and a self-reported history of animal abuse perpetration in a sample of 214 jail inmates. Analyses indicated individuals who endorsed a history of animal abuse scored significantly higher than non-abusers on the PCL:SV total score. Indeed, the results also suggested significant differences across the facets of psychopathy. Regarding personality pathology, results did not show any significant association with the domains of personality pathology.